Local adaptation of aluminum blanks through laser de-alloying and wire alloying - Stephan, Marcel; Zieroth, Henrik; Samland, Simona; Bartels, Dominic; Merklein, Marion; Schmidt, Michael (SheMet2025, 2025)
Abstract. The 7xxx series aluminum alloys, renowned for their exceptional specific strength, are promising materials for automotive manufacturing. Despite their advantages, the widespread application of these alloys is inhibited by their low formability. The high strength but low formability is caused by Zn and Mg precipitations, which hinder dislocation motion. In this study, the local adaption of the elemental composition of aluminum blanks through selective evaporation and alloying via auxiliary wire is investigated. A high-power laser is used for melting and evaporating low boiling elements such as Mg and Zn while adding AlSi5 in parallel to improve formability in the forming zone. The resulting element distribution is studied and correlated with the applied process conditions, to gain an insight on the possibilities and limitations of the laser induced alloy adaptio
Keywords: Laser Welding; Aluminum; Hybrid Manufacturing